This House Is My Love Letter - Navarro, Louie T. (Likhaan: The Journal of Contemporary Philippine Literature, 2024)
A stream-of-consciousness approach takes this essay into a tumultuous account of a designer-client relationship complicated by the fact that each is one-half of a long-term romantic partnership. Written from the point of view of the designer (ala Barthes’ lover vis-à vis the beloved to whom this letter is addressed), the design processes that define the professional practices under the built environment cluster— drawing, material specification, punch-listing—are collapsed with the personal—frustrations, angst, hope—in this work that borders the confessional.Starting from the initial design phase, to the construction, and all the way to the occupancy of the finished project, this essay is ultimately centered on the unpacking of the complexity inherent in any collaboration, whether platonic or otherwise—furthered as it were here by the premise of the house as one of the more concrete expressions of love.